Peak fat oxidation rate during walking in sedentary overweight men and women - Bogdanis, G.C.a b , Vangelakoudi, A.a , Maridaki, M.a (Journal of Sports Science and Medicine, 2008)
{The aim of this study was to determine the relative exercise intensity that elicits maximal fat oxidation during walking in inactive and overweight men and women and evaluate any possible sex differences. Forty six healthy, sedentary, overweight men (age: 36.3±1.3 years, body fat: 28.8 ± 0.8%